2016
DOI: 10.18632/oncotarget.13990
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of COX-2 immunohistochemical expression in breast cancer: a meta-analysis

Abstract: The prognostic significance of COX-2 in patients with breast cancer remains controversial. The aims of our meta-analysis are to evaluate its association with clinicopathological characteristics and prognostic value in patients with breast cancer. PubMed, EMBASE, Web of Science, the Ovid Database and Grey literature were systematically searched up to May 2016. Twenty-one studies including 6739 patients with breast cancer were analyzed. The meta-analysis indicated that the incidence difference of COX-2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 43 publications
(23 reference statements)
0
23
1
Order By: Relevance
“…A recent meta-analysis including 21 studies and 6739 patients with breast cancer showed that the presence of high levels of COX2 predicts a greater tumor size and lymph node metastasis (11). The occurrence of COX2-overexpressing tumors in each study ranged from 27.9% to 81.4%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent meta-analysis including 21 studies and 6739 patients with breast cancer showed that the presence of high levels of COX2 predicts a greater tumor size and lymph node metastasis (11). The occurrence of COX2-overexpressing tumors in each study ranged from 27.9% to 81.4%.…”
Section: Discussionmentioning
confidence: 94%
“…The occurrence of COX2-overexpressing tumors in each study ranged from 27.9% to 81.4%. As illustrated by this meta-analysis (11), most published studies on prognostic or predictive value of COX2 were performed using immunohistochemistry. But the methods used for immunohistochemical analysis of COX2 were diverse, with various antibodies, lack of standardization of staining, and analysis of tumor COX2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the COX-2 peroxidase activity may contribute to production of mutagens ( Figure 1). [5][6][7][8] Enhanced COX-2 expression was demonstrated in various types of human malignancies: carcinomas of colon, 9,10 breast, 11,12 lung, 13,14 stomach, 15,16 esophagus, 17,18 pancreas, 19 bladder, 20 prostate, 21 ovary, 22,23 cervix, 24,25 osteosarcomas, 26,27 gliomas, 28,29 and Hodgkin lymphomas. 30 In most of the studies, it was shown that cancer progression is accompanied by an increase in COX-2 levels and may have prognostic potential.…”
Section: Cyclooxygenase-2 In Cancermentioning
confidence: 99%
“…Although up-regulated COX-2 contributes to tumor development ( 2 ), the extent of COX-2 distribution vary among individual studies ( 3 , 4 ). For instance, in invasive breast carcinoma, the reported frequencies of COX-2 detection by immunohistochemistry range from 17% to 84%, with a pooled estimate of 42% ( 3 ).…”
Section: Introductionmentioning
confidence: 99%